INDICATORS IN PHYSICAL FITNESS LEVELS OF SCHOOL TEENS FEDERAL INSTITUTE OF ALAGOAS - IFAL (Fiep Bulletin - online, 2012)
The aim of the study was a survey of health indicators such as level of physical fitness andlevel of muscular endurance (RML) of students at Federal University of Alagoas - IFAL.The sample consisted of 83 students IFAL, 42 girls and 41 boys, mean age between 14and 17. For data collection, we used: the test of 12 minutes Cooper test and abdominalPollock. The results showed that the vast majority is classified as very weak physically. We can conclude that the tests were of paramount importance, for the low results between indicators of physical fitness and muscular endurance of adolescent students IFALCampus Maceió, point to very weak most of the students of agreements with other research findings.
Keywords: Physical Activity; Physical Fitness; muscular endurance